2015
DOI: 10.1080/03069885.2015.1072128
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between alexithymia and Machiavellian personality beliefs among university students

Abstract: The present study considered the relationships between alexithymia and Machiavellian personality beliefs among university students. Two hundred and thirteen students (95 women and 118 men) studying Master's degrees in psychology, education, law, political sciences, and social sciences at the University of Tehran were randomly chosen using multi-stage clustering sampling and screening. Participants completed the Kiddie Mach scale and Toronto Alexithymia scale (Persian version). Data were analysed by Pearson's c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Trait Machiavellianism is associated with increased amorality (Sheikhi, Issazadegan, Norozy, & Saboory, 2017). Machiavellianism is also related to manipulative relationship behaviours, such as sexual deception and infidelity (Brewer & Abell, 2015).…”
Section: The Dark Triad and Emotional Manipulationmentioning
confidence: 99%
“…Trait Machiavellianism is associated with increased amorality (Sheikhi, Issazadegan, Norozy, & Saboory, 2017). Machiavellianism is also related to manipulative relationship behaviours, such as sexual deception and infidelity (Brewer & Abell, 2015).…”
Section: The Dark Triad and Emotional Manipulationmentioning
confidence: 99%
“…In women, testosterone application affected emotional functions ( 73 ), enhanced responsiveness to social threat ( 74 ), and diminished cognitive empathy ( 75 ). Moreover, Machiavellian trait patterns [which are significantly associated with alexithymia; e.g., ( 76 )] interacted with the application of testosterone and AVP and modulated aggression levels ( 77 ).…”
Section: Hormone Studies In Alexithymiamentioning
confidence: 99%
“…According to a study, individuals with a high level of Machiavellianism exhibit more damaging behaviors. In addition, it has been argued in some studies that Machiavellian individuals violate ethical norms and moral rules more, tell lies, are prone to deceptive and unethical behaviors, prioritize their individual interests, and are emotionally cold individuals [9,[11][12][13][14]. It has also been reported that Machiavellian individuals pay less attention to principles and criteria [14].…”
Section: Introductionmentioning
confidence: 99%